2020
DOI: 10.2196/13392
|View full text |Cite
|
Sign up to set email alerts
|

A Culturally Adapted Cognitive Behavioral Internet-Delivered Intervention for Depressive Symptoms: Randomized Controlled Trial

Abstract: The CONSORT-EHEALTH checklist is intended for authors of randomized trials evaluating webbased and Internet-based applications/interventions, including mobile interventions, electronic games (incl multiplayer games), social media, certain telehealth applications, and other interactive and/or networked electronic applications. Some of the items (e.g. all subitems under item 5description of the intervention) may also be applicable for other study designs.The goal of the CONSORT EHEALTH checklist and guideline is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 89 publications
2
35
0
Order By: Relevance
“…In one study, 41 three patients in the Indian sample population reported abdominal discomfort, which was judged to be possibly related to the study medication, and one patient experienced an exacerbation of psychosis after having missed one dose of depot neuroleptics. The remaining 18 studies [28][29][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45]47,49,50 did not report on adverse events. (1) Online intervention group: participants used a simple and rapid interactive website (ASSIST-MBIc) that was constructed to mirror the content of the interview intervention; the website consisted of an initial screening questionnaire based on the self-report format of ASSIST, explanations of screening scores, and the inclusion of fictitious drug names.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, 41 three patients in the Indian sample population reported abdominal discomfort, which was judged to be possibly related to the study medication, and one patient experienced an exacerbation of psychosis after having missed one dose of depot neuroleptics. The remaining 18 studies [28][29][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45]47,49,50 did not report on adverse events. (1) Online intervention group: participants used a simple and rapid interactive website (ASSIST-MBIc) that was constructed to mirror the content of the interview intervention; the website consisted of an initial screening questionnaire based on the self-report format of ASSIST, explanations of screening scores, and the inclusion of fictitious drug names.…”
Section: Resultsmentioning
confidence: 99%
“…Only seven studies 30,32,38,42,44,46,47 described which procedures of allocation concealment were used. With regards to reporting bias from selective outcome reporting, 13 studies 27,[29][30][31][32]38,40,42,44,46,47,49,50 provided trial registration information. Regarding attrition bias, 13 studies [27][28][29][30][31][32]37,38,40,41,44,46,47 reported a reasonable method to eliminate potential bias caused by missing data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arjadi and colleagues ( 33 ) applied the Ecological Validity Model to adapt an internet-based behavioral activation intervention addressing depression for Indonesian people. In addition, an internet-based intervention for depression was culturally adapted for Colombian university students using this model ( 34 ) and was evaluated ( 35 ). Evidence from a meta-analysis of eight randomized controlled trials showed that the effectiveness of minimally guided digital mental health interventions to reduce symptoms of common mental disorders was enhanced by cultural adaptation ( 36 ).…”
Section: Introductionmentioning
confidence: 99%